Phytoplankton diversity and abundance in San Pedro Bay and Maqueda Bay during the "red tide" event in 2015 - Castaños, Gwen Karen C.; Yap-Dejeto, Leni G. (2016)
During October 2015, a "red tide" event, scientifically known as "Harmful Algal Blooms (HABs)", occurred in Eastern Visayas. Coastal communities were threatened by toxic algal blooms of Pyrodinium bahamense var. compressum (Pbc) which hospitalized 22 victims and caused the death of a 7-year old boy. People in coastal communities depend mainly on marine waters as a source of food and livelihood. Thus, it is imperative to provide information on the degree of Pbc bloom. Pbc ecology is also needed to further understand Pbc blooms. Consequently, other phytoplankton species present during the red tide event and the cell densities of each species should be known. The study identified and quantified the phytoplankton species present in San Pedro Bay and Maqueda Bay during the red tide event. A 20 um sized plankton net was used for taking water samples for qualitative analysis while the bucket method was followed for quantitative analysis. Physicochemical parameters were also assessed. The water samples were further processed for phytoplankton identification, cell count and cell density determination. Results showed that in Motiong station alone in Maqueda Bay, Pbc count was at 5.1x10 raised to the power of 4 cells/L while adjacent San Pedro Bay remained free from Pbc. Instead, it was dominated by Bacillaria paxillifera with an average cell density of 5.4x10 raised to the power of 3 cells/L. Several factors such as depth, salinity, pH and presence of other phytoplankters that probably cause the bloom of Pbc in Motiong are discussed in the paper.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology